Penerapan Model Pembelajaran Problem Based Learning Berbasis Sosiodrama Pada Mata Pembelajaran PPKn Untuk Meningkatkan Hasil Belajar Siswa Kelas 3 SDN Ngrambe 2 - Prismawinda Anifa Nudqi; Wasilatul Murtafiah; Radityarisma Mahardika (Universitas Sarjanawiyata Tamansiswa, 2023)
School is a formal educational institution that acts as a place for students to learn in gaining knowledge to increase their potential, success in learning lies in the results of student achievements. One of the success factors of learning carried out by the teacher is the existence of a learning model that is appropriate to the circumstances and conditions of students. This Classroom Action Research aims to improve students' Civics learning outcomes. This research was conducted in two cycles. Each cycle consists of planning, implementing, observing and reflecting. The results showed an increase in civic education learning outcomes, cycle 1 of 66.67, and cycle 2 of 86.1. The sociodrama-based PBL model needs to be applied in Civics learning to improve student learning outcomes.